Temples of Books: Magnificent Libraries Around the World - Strauss, Marianne Julia; Klanten, Robert; Elli, Stuhler (Berlin: Gestalten, 2022)
Libraries are so much more than collections of books. They are archives of knowledge, spaces of study, sources of inspiration and connection. Among the world's most universal and democratic places, they are also outstanding icons of architecture that represent the societies that built them.Temples of Books celebrates the world's oldest and grandest shrines to the written word, as well as new and tiny ones: from baroque palaces to micro-libraries made of recycled plastics, and the unlikely ones in between.Looking at the diverse architecture of global libraries throughout the ages, Temples of Books goes further and explores the very idea of libraries themselves.
Keywords: Library Architecture -- Library Buildings